The role of metal–support interaction in Ag/CeO2 catalysts for CO and soot oxidation - Grabchenko, M.V.; Mamontov, G.V.; Zaikovskii, V.I.; La Parola, V.; Liotta, L.F.; Vodyankina, O.V. (Applied catalysis. B, Environmental, 2020)
[Display omitted] •Method of preparation of Ag/CeO2 catalysts determines the features of the MSI.•Redox reaction between Ce3+ and Ag+ during catalyst synthesis lead to MSI.•Epitaxial growth of Ag NPs (d111 = 2.35 Å) occurs on CeO2 surface (d111 = 3.1 Å).•Enhanced interfacial Ag–CeO2 interaction increases the amount of active oxygen species.•MSI in Ag/CeO2 catalysts enhances their activity in CO and soot oxidation. Ag/CeO2 catalysts with a silver loading of 10 wt.% have been prepared by three different techniques: impregnation, Ag/CeO2 (imp), impregnation of prereduced CeO2, Ag/CeO2 (red-imp), and co-deposition precipitation, Ag-CeO2 (co-DP). The features of the prepared composites have been studied by low-temperature N2 sorption, TGA, XRF, TPR-H2, TEM HR, XPS and Raman spectroscopy. The Raman and XPS results show that the addition of silver to CeO2 significantly increases the defectiveness of CeO2 particles, and such an effect is a function of the preparation method. The Ag-CeO2 (co-DP) and Ag/CeO2 (red-imp) catalysts show enhanced interfacial Ag–CeO2 interaction caused by the epitaxial growth of silver particles (d111 = 2.35 Å) on the CeO2 surface (d111 = 3.1 Å) as well as high amount of oxygen vacancies. A morphology-dependent interplay between the oxygen vacancies and the strength of the Ag–CeO2 interaction has been revealed. Strengthening of the metal–support interaction enhances the catalytic activity of the composites in both CO oxidation and soot combustion.